Statistical Performance Analysis of a 20 kV Circuit Breaker at Bangka Substation - Putri, Tiara Dela; Puriza, M. Yonggi; Asmar, Asmar; Sunanda, Wahri (Jurnal Inovasi Teknologi, 2025)
This study evaluates the performance of 20 kV circuit breakers by analyzing insulation resistance, contact resistance, contact synchronization, leakage current, and power loss. The insulation resistance analysis indicated that phases R and S did not show significant improvement after maintenance, with significance values of 0.065 and 0.166, respectively, while phase T exhibited a significant improvement with a significance value of 0.048. Contact resistance measurements revealed no statistically significant reductions after maintenance, with significance values of 0.209, 0.243, and 0.155 for phases R, S, and T, respectively. Additionally, contact synchronization in the open condition did not experience significant variations, whereas in the closed condition, all phases showed significant declines in synchronization after maintenance, with significance values of 0.003, 0.013, and 0.007. Leakage current analysis at a 20 kV phase-to-ground voltage showed that the highest recorded leakage current was 0.297 mA in the Eks Sumberejo feeder, significantly below the 20 mA threshold. Power loss calculations identified the highest power dissipation in the Depati Hamzah feeder at 69.87 W, with the lowest in the Eks Transmart feeder at 0.376 W. Energy loss assessment further showed the Depati Hamzah feeder experiencing the highest loss at 48.317 kWh, while the Eks Transmart feeder had the lowest at 0.278 kWh. These findings underscore the importance of routine monitoring and targeted maintenance to enhance circuit breaker reliability, optimize operational efficiency, and minimize energy losses in high-voltage electrical networks.